2020
DOI: 10.1186/s12544-020-00404-y
|View full text |Cite
|
Sign up to set email alerts
|

Which factors affect willingness-to-pay for automated vehicle services? Evidence from public road deployment in Stockholm, Sweden

Abstract: Introduction: Travel demand and travel satisfaction of a transport service are affected by user perceptions of the service quality attributes, and such perceptions should be included in studying user willingness-to-pay (WTP) for automated vehicle (AV) services. This study applied structural equation modelling with service quality attribute perceptions as latent variables affecting WTP. Objectives: We investigated how WTP AV services are affected by socio-demographic characteristics, knowledge and experiences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…In general, it can be said that the results do not show a willingness to pay a price for an AS service that is significantly higher than the average amount paid for services carried out with traditional transport systems. This is partially in line with the results obtained by Chee et al [65], which found a WTP for automated bus service in urban contexts not higher than the average cost for traditional public transport services for 44% of the respondents in their sample. These results show a considerable confidence of potential users for the technology used in AS, but with regard to the willingness to pay they seem to identify the proposed vehicle more with the service provided than with its inherent technological characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…In general, it can be said that the results do not show a willingness to pay a price for an AS service that is significantly higher than the average amount paid for services carried out with traditional transport systems. This is partially in line with the results obtained by Chee et al [65], which found a WTP for automated bus service in urban contexts not higher than the average cost for traditional public transport services for 44% of the respondents in their sample. These results show a considerable confidence of potential users for the technology used in AS, but with regard to the willingness to pay they seem to identify the proposed vehicle more with the service provided than with its inherent technological characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…While intermodal commuters, combining PT and the car, are most open to shared (automated) services, people commuting solely with PT are least open. In line with the results by Chee et al [14], the study thus shows that current commuter mode choice is a relevant predictor of the acceptance of new car-based mobility services.…”
supporting
confidence: 89%
“…The third paper by Chee et al [14] examined the potential use of different automated vehicle (AV) services, or more specifically, which factors affect the willingness to pay for their use. Apart from a first/last mile automated bus service that was already in operation as part of an AV trial in Sweden, on-demand personalized AV services and demand responsive shared AV services were considered.…”
mentioning
confidence: 99%
“…For further extensive reviews of the plausible impacts of automated vehicles, McGehee et al (2016), Milakis et al (2017), Innamaa et al (2017) and the MANTRA (2019) project report provide a comprehensive description of the plausible societal impacts and policy implementation challenges. Hoogendoorn et al (2014) discussed the roles of human factors and expected traffic impacts; Chee et al (2020a) and Nordhoff et al (2019) reported on automated vehicle (AV) technology acceptance for daily travel; and Do et al (2019) reported on design and control of the automated vehicle system. More recently, Soteropoulos et al (2019) provided a systematic overview of different modelling approaches that have been used to explain the impacts of automated vehicles on travel behaviour and land use characteristics.…”
Section: Human City and Automated Futurementioning
confidence: 99%
“…Light detection and ranging (LIDAR) data 1 for a limited time was collected in order to get a glimpse of the interaction between the automated bus and pedestrians, private cars and other road users, in the given road space. The complete analyses of each of these cases can be seen at Chee et al (2020aChee et al ( , 2020bChee et al ( , 2021.…”
Section: Users' Intentions Expectations and Reactionsmentioning
confidence: 99%